Implikasi Zakat dan Islamic Social Reporting Terhadap Kinerja Keuangan Pada Perbankan Syariah Di Indonesia - Puji Nurhayati; Dian Saputri Rustiningrum (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to determine the effect of Zakat and Islamic Social Reporting on the financial performance of Indonesian Islamic banking listed on the Jakarta Islamic Index (JII) for 5 years from 2015-2019. The population in this study is Islamic banking which recorded in the Jakarta Islamic Index (JII) for the 2015-2019 period. Sampling technique using purposive sampling method and obtained 70 islamic banking which is used as a sample. Data analysis technique using panel data regression analysis technique using eviews. Statistical analysis in this study uses quantitative data. The results of this study indicate that: Zakat has no effect on Islamic banking financial performance, Islamic Social Reporting (ISR) has an effect on financial performance in Islamic banking, Suggestions for further research can add research variables and increase the research period so that the results obtained are more accurate.